Induced chemical and physical mutagenic studies in M1 generation of French bean (Phaseolus vulgaris L.) - Mahamune, S E; Kothekar, V S (Current Botany, 2012)
The seeds of French bean varieties Varun and Waghya were treated with chemical mutagens EMS and SA and physical mutagen gamma rays. M1 generation was raised and studied with respect to different morphological parameters such as germination percentage, seedling height, leaf morphological changes, chlorophyll chimeras, pollen sterility and plant survival percentage at maturity. An increasing trend with an increase in mutagenic concentrations/doses could be recorded for leaf morphological changes, chlorophyll chimeras and pollen sterility while germination percentage, seedling height and plant survival percentage at maturity revealed decreasing trend with increasing mutagenic concentrations/doses.